THE EFFECTIVENESS OF THE USE OF DIGITAL TECHNOLOGIES IN THE FIELD OF LOGISTICS (World Bulletin of Management and Law, 2023)
This article discusses the concept and content of the digital transformation of logistics; problems of introducing digital technologies in logistics, analysis of the prospects for digital technologies in logistics, Types of digital logistics systems in the supply chain